A formação de professores de Língua Estrangeira Moderna - Espanhol - para atuação na escola do campo - Riedner, Viviane (2016)
This descriptive-qualitative study of case is presented as a research of bibliographical and field nature. As such, it attempted at correlating the thematic of the Spanish Teachers Training and the Education for Brazilian Schools in the country area, called Country Schools, under the perspective of the Rural Sustainable Development. The main aim of the present study was to offer an articulation of these thematic, seeking to motivate the construction of a meaningful and interdisciplinary Spanish Teaching and Learning Process. The inquiring was carried out in the Maralúcia Country State School, in Maralúcia district of Medianeira City, Paraná State. The locus of the study was the Center of Foreign Languages Teaching (CELEM). The analytic corpus was formed mainly by a questionnaire applied to the participants: a teacher and her students from the Spanish Language Course in CELEM. The data were analyzed by the content analysis technique Bardin (2011), and revealed the following aspect: although the teacher recognizes a lack in her academic training for teaching in the Country School level, and hence she considered herself not being prepared to teach the contents of the Environment Education, most of the investigated students showed having some knowledge about the issues of the environment protection and rural sustainable development. All of these students identified the local biodiversity problems, and indicated possible strategies to solve them in order to ensure the sustainable life in the investigated area. The study also indicated that such knowledge comes from the Maralúcia engagement in projects that have been developed by the school and the local community. In respect to the theoretical and methodological reflections it was identified some differences and contradictions about the public politics for the teachers training and for the sustainable development in the rural area. The final results of the research pointed such important aspects: the relevance of empowering the Spanish Teachers Training for the needs of the Education in the Country Schools; the call for politics of Environmental Education; the needs of reinforcing the construction of interdisciplinary projects for contemplating the issues of the Rural Sustainable Development; and also the significance of recognizing the local community support in order to propitiate this integrated practice